Gap between maternal preferences and actual mode of delivery in Agra District of Uttar Pradesh: observational study - Arti Verma; Pooja Verma; Preeti Gupta; Prathyusha Lingareddy (International Journal Of Community Medicine And Public Health, 2026)
Background: The raising trend of cesarean section deliveries worldwide is a matter of concern. Most of the women prefer normal institutional normal vaginal delivery but their actual mode of delivery depends on their obstetric and healthcare factors. Objective was to assess the gap between preference and practice regarding the delivery mode and to identify factors associated with delivery against maternal preference among women in Agra, Uttar Pradesh. Methods: A community based cross sectional study conducted among women who had delivered a live baby within the previous one year in selected rural and peri-urban areas of Agra district. A multistage stage random sampling, 300 women were interviewed with pre tested and structured questionnaire, 272 institutional deliveries were included. Data on socio-demographic characteristics, obstetric history, antenatal care and preference were collected and analyzed using descriptive statistic, chi- square test fisher’s exact test and logistic regression analysis using JAMOVI software. Results: Out of 272 deliveries, 223 (82.0%) were normal vaginal and 49 (18.0%) were cesarean section. Most women (97.4%) preferred normal delivery. Maternal education, husband’s education, parity, previous mode delivery and type of health facility were significantly associated. Logistic regression identified place of delivery (AOR=2.93, p=0.004) and previous mode delivery (AOR=7.69, p